Information and psychological operations as one of the types of threats to information security of Ukraine - Yakovenko, K. V.; Zviertsev, H. A. (Національний авіаційний університет, 2024)
The paper examines the main types of information and psychological operations (fake news , disinformation, exaggeration or understatement of information, bot cyberattacks, propaganda) and analyzes their potential harm to Ukraine's information security.
Keywords: information and psychological operations (PSYOP); information security; Russian-Ukrainian war; fake news; disinformation; propaganda